Analysis of Preservatives in Packaged Drinks with Chromatography Techniques - Merry Yunita (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
A research has been conducted on qualitative and quantitative of soft drinks preservative analysis. The analysis used chromathography. The calibration kurve of real standard was used to determine the concent of preservative. The concents of the drinks preservative would be suitable for the standard of preservative of Minister of Publik Health R.I No. 722/Menkes/per/IX/1988. The data was analyzed by using correlation and signification method between area and concentration and the result of the research has fulfilled quality standard of preservative